Historical Water Infrastructures of Hanuman Dhoka Durbar Square - Sthapit, Suraj (Nepalese Culture, 2026)
The country of Nepal was united and divided in its several phases. When divided, the country had many small principalities along with their respective palaces as well. Accordingly, the valley of Kathmandu was also divided into three kingdoms. Hanuman Dhoka Durbar Square was the palace of Kantipur and the unified country of Nepal as well and is now accorded a UNESCO world heritage status due to its art, architecture, intangible culture and so on. Despite the prevalence of many research on several aspects of the palatial complex, none accounts the historical water infrastructures of the palace complex. In this context, an exploratory research to identify historical water infrastructures and to understand their use cases explores the palace in new way through this research. Data is collected basically through observation and photography of each are provided as solid evidence. The use cases of each infrastructures are collected through interview and observation as well. From this research, it is identified that there are in total four stone spouts, of which two are copper plated; six Jahruhiti, two ponds, seven wells, five toilet basins and not a single historical kitchen could be located from the palatial complex. Majority of the land-use inside the palace is rendered impermeable due to stone pavement joined with modern concrete expect for four courtyards that possess brick pavements and two zones are fully permeable. In three instances rainwater harvesting is performed. The use cases of Jahruhiti in modern time is obsolete but in history acted as water tanks for public which was filled manually. Among four stone spouts, two were sources for the pond and other two was used for ritual and worship purposes. Some wells served ritual worship to their respective temples while others were used for general purpose.